PENERAPAN MODEL PEBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA 3 DIMENSI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMP N 1 KAMBATA MAPAMBUHANG - Huki Radandima, Marselinus; Makaborang, Yohana; Rambu Hada Enda, Riwa (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the in academic achievement or learninig outcomes of student by implemeting the Project Based Learning (PjBL) learning model class VIII plant structure and function subjects at SMP N 1 Kambata Mapambuhang. The population of this research is all student in class VIII of SMP N 1 Kambata Mapambuhang. In collecting data in this research, observation sheets and multiple choice test questions were used. By comparison, it can be seen that cycle II experienced a increase in the cogitive and psychomoral domains. By looking at the percentage of student who use the Project Based Learning (PjBL) learning model assisted by 3-dimensional media in class VIII at SMP N 1 Kambata Mapambuhang has icreased from pre-cycle, cycle I, and cycle II.